Digital Audio Workstation (DAW) As A Technology Communication Medium in the Convergence of Music Production Practices in the Digital Age - Ario Prabowo; Citra Pratiwi (Riviera Publishing, 2026)
The rapid development of digital technology has significantly transformed the music industry, particularly in the processes of production, distribution, and consumption. One of the key innovations driving this transformation is the Digital Audio Workstation (DAW), which enables musicians to produce music independently within a flexible and digital ecosystem. This research analyzes the role of the Digital Audio Workstation (DAW) in the convergence of technology and music production practices in the digital era. DAW is not only a music production tool but also serves as a communication medium that shapes musicians’ creative patterns. Using McLuhan’s technological determinism theory and Jenkins’ media convergence theory, the study finds that DAW introduces flexibility in music production, allowing cross-border collaboration. The results indicate that DAW has democratized music production, enabling independent musicians to control both the creative process and music distribution, although challenges such as digital literacy and quality standards remain. DAW plays a crucial role in shaping musicians’ identities, facilitating communication with audiences, and accelerating the emergence of a more collaborative and global digital music culture. This research also shows how DAW transforms the way musicians interact with technology and the broader music industry.